(untitled) (Research, Society and Development, 2022)
The babassu mesocarp has a high content of starch, which is not used biotechnologically in the Amazon. Obtaining rhizobacteria capable of converting this starch into glucose can strengthen the production chain of this palm, placing it as one of the plant species to contribute to the Amazon bioeconomy. This work evaluated the effect of pH 4.0, 5.0, 6.0 and 7.0 and temperatures of 27 °C and 55 °C on the ability of five Amazonian rhizobacteria to produce glucose using the babassu mesocarp. Rhizobacteria INPA R015, INPA R028, INPA R034, INPA R 236 and INPA R269 converted starch to glucose at all tested pHs and temperatures. The presence of amylolytic activity at a temperature of 55 °C shows that they can be used in industrial processes at high temperatures, when there is less possibility of contamination by mesophilic microorganisms. There was a significant influence of media pH and incubation temperatures on glucose production, which ranged from 3.02 to 8.66 gL-1, with the lowest occurring 24 hours after the beginning of the experiment using INPA R269 at a temperature of 27 ºC and pH 5.0 and, the highest, with the same bacteria and temperature, but in the medium with pH 7.0 after 96 hours of incubation. The presence of glucose in the media indicates that these five rhizobacteria show potential to be used for biotechnological purposes using babassu flour for their growth, strengthening the production chain of this palm tree that is little used in the Amazon. Further studies are needed, such as whether mixtures with these rhizobacteria allow greater production of glucose than the production of each one of them individually.